Numerical analysis of waves attenuation by vegetation in enclosed waters - Mattosinho, G. O.; Maciel, G. F. [UNESP]; Vieira, A. S.; Fortes, C. J. E. M.; Soares, C. G.; Santos, T. A. (Crc Press-balkema, 2018)
Numerical simulations using the SWAN-VEG model (Simulating WAves Nearshore, with vegetation module) were performed considering the case of Ilha Solteira (SP) reservoir, a navigable stretch of the Tiete-Parana waterway. The objective was to analyse the attenuation of wind-generated wave energy by the presence of vegetation in the left margin of reservoir (place of higher simulated wave heights). In this analysis, we varied the vegetation parameter, V-f, different submergence ratios and the wind intensity for NE wind direction. The results pointed up a neglegible influence of mesh size but high wave attenuation coefficients due the presence of vegetation. Application of non-structural measures to the attenuation of waves in these areas is plausible and should be encouraged because in addition to producing high attenuation coefficients, this is in general a cheaper and environmentally friendly solution.